Is (3599) Basov a large C-type super-fast rotator?. (1st October 2022) - Pan, Kang-Shian; Ip, Wing-Huen; Lin, Chia-Lung; Huang, Li-Ching; Cheng, Yu-Chi; Yeh, Ting-Shuo
Abstract: The rubble-pile model of asteroids deduced from the existence of a spin cutoff is an important paradigm in the interior structure of asteroids as a consequence of their collisional evolution. Many objects with size less than 200 ​m have been found to be rotating with a spin period less than 2.2 ​h but seldom so for bigger objects. Thus, asteroids with rotation periods significantly less than this spin cutoff limit are called super-fast rotators. Most often this picture of spin cutoff and hence the rubble-pile model has been applied to the S-type asteroids. In this study, we report the interesting case of (3599) Basov which is a member of the Themis family of C-class composition. The spin barrier of the Themis family asteroids has been shown to be P ​= ​3 ​h. What is unusual about (3599) Basov is that its rotation period has been confirmed to be P ​= ​2.157 ​± ​0.037 ​h which is significantly shorter than the critical value for centrifugal breakup. Furthermore, its size of 18 ​km is much larger than those of the S-class super-fast rotators. The physical property of (3599) Basov might therefore be quite unique. Highlights: C-type asteroids of rubble-pile structure should have a spin-cutoff at about 3 h The rotation period of (3599) Basov is confirmed to be P=2.157±0.037 h and a C-type asteroid by photometry and spectroscopy observations. If (3599) Basov has a rubble-pile structure, it should not have such a short rotation period unless it has a very large cohesive force.